Monozygotic twins discordant for frontonasal malformation. - Mohammed, SN; Swan, M; Wall, SA; Wilkie, A (2004)
Frontonasal malformation (FNM), also known as the median cleft face syndrome, encompasses a spectrum of phenotypes that are believed to result from a single underlying aetiology. Over the course of two decades, the Craniofacial Unit at the Radcliffe Infirmary, Oxford has been involved in the management of six same-sex twins where only a single twin is affected. With local ethical committee approval, five sets of twins were traced and consented to participation in this study. Monozygosity of all five twin pairs was confirmed, and the clinical features were reviewed. We discuss the mechanistic relationship between FNM and the twinning process and the genetic implications of this association.